(+)-Grandifloracin, an antiausterity agent, induces autophagic PANC-1 pancreatic cancer cell death - Ueda, Jun-ya (Dove Medical Press, 2013)
Human pancreatic tumors are known to be highly resistant to nutrient starvation, and this prolongs their survival in the hypovascular (austere) tumor microenvironment. Agents that retard this tolerance to nutrient starvation represent a novel antiausterity strategy in anticancer drug discovery. (+)-Grandifloracin (GF), isolated from Uvaria dac, has shown preferential toxicity to PANC-1 human pancreatic cancer cells under nutrient starvation, with a PC(50) value of 14.5 μM. However, the underlying mechanism is not clear. In this study, GF was found to preferentially induce PANC-1 cell death in a nutrient-deprived medium via hyperactivation of autophagy, as evidenced by a dramatic upregulation of microtubule-associated protein 1 light chain 3. No change was observed in expression of the caspase-3 and Bcl-2 apoptosis marker proteins. GF was also found to strongly inhibit the activation of Akt, a key regulator of cancer cell survival and proliferation. Because pancreatic tumors are highly resistant to current therapies that induce apoptosis, the alternative cell death mechanism exhibited by GF provides a novel therapeutic insight into antiausterity drug candidates.